Generating change from below: what role for leadership from above? - King, Fiona; Stevenson, Howard (Emerald, 2017)
In recent years the benefits of distributed leadership have often assumed the status of an unchallengeable orthodoxy. There is a general acceptance that leadership is best when it is dispersed. In reality this is often little more than a form of ‘licensed leadership’ in which those working in subordinate roles can only exercise their leadership in tightly prescribed contexts. This article investigates the contribution of teacher professional development to promoting a more optimistic vision of teacher leadership and, ultimately, organisational change. It explores the role of leadership ‘from above’ in supporting classroom teachers to engage with and sustain change.